Actual aspects of extragenital pathology: focus on insufficiency of the secretory function of the thyroid gland and dysfunctional disorders of the biliary tract - Mariia Yu. Rozhkova; Dmitry I. Trukhan; Daria S. Ivanova; Viktoriia V. Goloshubina (LLC "MEDIAFORMAT", 2023)
An important aspect of preconception preparation is the assessment of a woman's health and the identification of extragenital pathology. In the presented review, there are two urgent problems related to the health of women of reproductive age, insufficient attention to which by the first contact doctor (therapist, general practitioner) can further complicate the course of pregnancy - a decrease in hormonal function of the thyroid gland and dysfunctional disorders of the biliary tract. The main pathogenetic links between the insufficiency of the secretory function of the thyroid gland and the functional state of the biliary tract are considered. It is advisable for first contact physicians, including as part of preconception preparation, to examine patients of reproductive age with biliary disorders for the possible presence of thyroid insufficiency, which will contribute to the early detection of extragenital pathology.